Cocultivation of Chinese prescription and intestine microbiota: SJZD alleviated the major symptoms of IBS-D subjects by tuning neurotransmitter metabolism - Xia, Xiuwen; Xie, Ya; Chen, Qiaoqiao; Ding, Dou; Wang, Zongqin; Xu, Yaji; Wang, Yili; Wang, Xiumin; Ding, Weijun (Frontiers in Endocrinology, 2022)
Objective: Diarrhea-predominant irritable bowel syndrome (IBS-D) is a recurrent and common disease featuring dysbiotic intestinal microbiota, with limited treatments. Si-Jun-Zi Decoction (SJZD), as a classic Chinese prescription, has been extensively used for IBS-D. This work aimed to explore the ex vivo interactions of SJZD and IBS-D’s intestinal microbiota. Methods: Five samples of intestinal microbiota collected from IBS-D volunteers and five age-matched healthy controls were recruited from the Affiliated Hospital, Chengdu University of Traditional Chinese Medicine (TCM). A representative mixture of intestinal microbiota was composed of an equal proportion of these fecal samples. To simulate the clinical interaction, this microbiota was cocultivated with SJZD at clinical dosage in an anaerobic incubator at 37°C for 35 h. Microbiota and metabolic alterations were assessed by 16S rDNA sequencing in the V3/V4 regions and a nontargeted metabolome platform, respectively. Results: After being cocultivated with SJZD, the dysbiotic intestine microbiota from IBS-D volunteers was largely restored to those of the healthy controls. A total of 624 differentially expressed metabolites were detected by nontargeted metabolomics, of which 16 biomarkers were identified. These metabolites were then enriched into 11 pathways by KEGG, particularly those involved in neurotransmitter metabolism responses for the major symptom of IBS-D. Correlation analysis of bacterial metabolites demonstrated a synergistic pattern of neurotransmitter metabolism between Streptococcus and E. Shigella. Conclusion: SJZD rescued the dysbiotic intestinal microbiota and ameliorated the dysfunctional neurotransmitter metabolism involved in the major symptoms of IBS-D.